Perancangan Purwarupa Pendeteksian Masker Menggunakan Mobilenetv2 dan Sensor Suhu GY-906 MLX-90614 Berbasis OpenCV - Lukman Medriavin Silalahi; David Martin Antoyo; Setiyo Budiyanto; Imelda Uli Vistalina Simanjuntak; Gunawan Osman; Agus Dendi Rochendi; Raden Sutiadi (Sekolah Tinggi Teknik - PLN, 2022)
The background of this research problem is the handling of the Covid-19 virus by using masks and regular body temperature measurements for each user entering/exiting a building. So this research aims to monitor people in carrying out the principle of using a mask and detecting a person's temperature with a limit not exceeding the normal temperature of 37.5 selsius. Outside of this research is the design of a face mask detection system and can measure a person's body temperature using Python programming that contains OpenCV, MobileNetV2 and gy-906 MLX 90614 non contact temperature sensors. the results of this research can be concluded that face mask detection can be done in the range of 50cm to 1.5m while face detection can be detected up to 3m when conducting real time testing and has a success rate of detecting face masks 86.6% to 93.3% from 15 times the experiments that have been conducted.